2008
DOI: 10.1017/s1751731108002413
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Escherichia coli infection of the bovine uterus from the whole animal to the cell

Abstract: Following parturition, contamination of the uterine lumen by bacteria is ubiquitous, and uterine health is impaired in cattle because infection persists in 10% to 15% of animals as endometritis. Endometritis causes infertility for the duration of infection, and subfertility persists even after apparent successful resolution of the disease. Escherichia coli is the pathogenic bacterium most frequently isolated from the post partum uterus, and is associated with increased concentrations of peripheral plasma acute… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
36
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 46 publications
(38 citation statements)
references
References 40 publications
0
36
0
Order By: Relevance
“…Kendall and others (2009) have suggested that animals with low progesterone values on day 7 are less likely to become pregnant. What is even more important in light of this study with respect to endometritis is the finding of Williams and others (2008) that uterine infection reduces luteal-phase progesterone values. Kendall and others (2009) were unable to improve pregnancy rates in repeat breeders with treatments designed to increase progesterone concentrations (CIDRs or human chorionic gonadotrophin injections) on days 5 or 6 after AI.…”
Section: Discussionmentioning
confidence: 68%
“…Kendall and others (2009) have suggested that animals with low progesterone values on day 7 are less likely to become pregnant. What is even more important in light of this study with respect to endometritis is the finding of Williams and others (2008) that uterine infection reduces luteal-phase progesterone values. Kendall and others (2009) were unable to improve pregnancy rates in repeat breeders with treatments designed to increase progesterone concentrations (CIDRs or human chorionic gonadotrophin injections) on days 5 or 6 after AI.…”
Section: Discussionmentioning
confidence: 68%
“…Furthermore, in the animals that ovulated, the CL was smaller and produced less progesterone (Figure 6; . Within the uterus E. coli may disrupt the mechanisms of PG-induced luteolysis in cyclic cows and therefore contribute to prolonged luteal phases by switching PG synthesis away from PGF2α towards PGE 2 (Herath et al, 2009;Williams et al, 2008b). These observations show a direct correlation between the presence of uterine pathogens, particularly E. coli, on day 7 postpartum and suboptimal ovarian function for the following 3 weeks.…”
Section: Postpartum Uterine Healthmentioning
confidence: 83%
“…F. necrophorum produces leukotoxin and P. melaninogenicus produces a substance which inhibits phagocytosis, which allows them to inhibit cell-mediated and humoral immunity, or both. It promotes the development of infections, and microorganisms may persist in the uterus for an extended length of time (Miller et al 2007, Williams et al 2008a,b, Sheldon et al 2010.…”
Section: Discussionmentioning
confidence: 99%